Analisis Pengaruh Sifat Fisis Lingkungan Terhadap Kualitas Buah Stroberi (Fragaria chiloensis) - Nurhayati Nurhayati; Jamrud Aminuddin; Rosi Widarawati (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2015)
This research studies about measurement of environmental physical characteristics such as temperature, humidity, and solar radiation which had done in strawberry field of Purbalingga, Jawa Tengah. The measurement had done to determine physical data values in the field and to give additional data for increasing the harvest productivity. The data had been aggregated by direct measurement in the field as long as 24 hours. Thus, the data are converted into a model which shows interpretation between the charracteristic parameter and time. Its result is used to make nonlinear interpolation in order to predict unmeasured values in this study. The study also measures the mass of the fruits for several sample. The results are analized comprehensively in environmetal physical characteristics and the fruits quality based on the additional data. These show that the ideal elevation field is 1297 m msl, temperature about 17.1-24.7 oC, humidity about 40.2-90.5 %, solar radiation ± 11 hours which gained at 06.00-17.00 WIB is 0-38x103 lxand fuits average mass in 16.779 g/fruit